CHINAS FOREIGN POLICY AND PRACTICE - Shao, Wenguang. ([S.l.])
1 online resource
Keywords: This book is one of the first wide-ranging surveys of China's foreign policy and practice from the 16th century to the present day from a Chinese perspective. A modern history of China's interaction with major powers, it throws new light on the events and issues of major interest, clarifies possible points of ambiguity and misunderstanding, and brings the reader up to date about some of the current issues of contention in China's international relations. China' Foreign Policy and Practice: Presents a unique account of Chinese statecraft and foreign policy from the vantage point of an insider who has spent years participating in the decisionmaking process at the national level; Paints a larger picture of China's interaction with the world, connecting wars, negotiations, treaties, and boundary settlements with its neighbours; Focuses on policy evolution in specific areas, such as trade, regional diplomacy, dispute settlement, crisis management, and engagement with major powers; Draws on Chinese records and publications that may not be readily accessible, as well as the latest memoirs and declassified documents; Is a nuanced, comprehensive and accessible guide for students of international politics as well as general readers interested in China. A unique history of China in world affairs, this book will be essential reading for students of politics and international relations, history, foreign policy, diplomacy, China studies, and Asian studies.